Determinants of Cottage and Small Industries Growth in Thimphu Thromde. - Tashi Norbu; Tendri Gyeltshen; Phuntsho Drukpa (Journal of Bhutan Studies)
The main purpose of this study was to investigate the determinants of the growth of Cottage and Small Industry (CSI) under Thimphu Thromde. We adopted a cross-sectional study design where samples were drawn using proportionate stratified random sampling technique. The analysis is based on the 102 CSI owners who responded to the online survey. Descriptive analysis shows that CSI sector in Thimphu Thromde is growing both in terms of employment generation and capital accumulation. Furthermore, multiple linear regression (MLR) test indicates that management know-how, technology, support CSIs get, and marital status are statistically significant with capital growth while access to finance, government rules and regulations and firm age were statistically significant with employment growth.